2012
DOI: 10.4103/0028-3886.98526
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment in startle epilepsy

Abstract: This report presents a patient with medically intractable startle epilepsy who was treated with surgery. The ictal onset zone was further localized to a part of the premotor cortex on the basis of intracranial electroencephalography recording and surgical resection of the epileptogenic zone was done. The motor area close to the epileptogenic focus was localized using electrical cortical stimulation and thus preserved. Patient has been seizure-free postoperatively (Engel Class I) during the 18-month follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For Chauvel and colleagues, startle epilepsy seizures thus originate in the motor and premotor cortices. Other recent studies reported a seizure onset zone located in the premotor cortex [21][22], the prefrontal cortex, and anterior and middle cingulate cortex [23]. The SMA was involved in the epileptic network of the majority of cases [21][22][23][24].…”
Section: Intracerebral Eeg Recordingsmentioning
confidence: 86%
See 4 more Smart Citations
“…For Chauvel and colleagues, startle epilepsy seizures thus originate in the motor and premotor cortices. Other recent studies reported a seizure onset zone located in the premotor cortex [21][22], the prefrontal cortex, and anterior and middle cingulate cortex [23]. The SMA was involved in the epileptic network of the majority of cases [21][22][23][24].…”
Section: Intracerebral Eeg Recordingsmentioning
confidence: 86%
“…Other recent studies reported a seizure onset zone located in the premotor cortex [21][22], the prefrontal cortex, and anterior and middle cingulate cortex [23]. The SMA was involved in the epileptic network of the majority of cases [21][22][23][24]. Using the Epileptogenicity Maps method, Job et al [18] identified an increase of high frequency oscillations in the premotor and prefrontal areas during startle epilepsy seizures and a constant involvement of the SMA.…”
Section: Intracerebral Eeg Recordingsmentioning
confidence: 97%
See 3 more Smart Citations